Permanent Gas Emission from the Seyakha Crater of Gas Blowout, Yamal Peninsula, Russian Arctic - Vasily Bogoyavlensky; Igor Bogoyavlensky; Roman Nikonov; Vladimir Yakushev; Viacheslav Sevastyanov (Energies, 2021)
The article is devoted to the four-year (2017–2020) monitoring of gas emissions from the bottom of the Seyakha Crater, located in the central part of the Yamal Peninsula (north of Western Siberia). The crater was formed on 28 June 2017 due to a powerful blowout, self-ignition and explosion of gas (mainly methane) at the site of a heaving mound in the river channel. On the basis of a comprehensive analysis of expeditionary geological and geophysical data (a set of geophysical equipment, including echo sounders and GPR was used) and remote sensing data (from space and with the use of UAVs), the continuing nature of the gas emissions from the bottom of the crater was proven. It was revealed that the area of gas seeps in 2019 and 2020 increased by about 10 times compared to 2017 and 2018. Gas in the cryolithosphere of the Arctic exists in free and hydrated states, has a predominantly methane composition, whereas this methane is of a biochemical, thermogenic and/or mixed type. It was concluded that the cryolithosphere of Yamal has a high level of gas saturation and is an almost inexhaustible unconventional source of energy resources for the serving of local needs.